2022
DOI: 10.1039/d1tc05506b
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-doped inorganic halide perovskites (CsPbX3): novel properties and emerging applications

Abstract: Inorganic halide perovskites (IHPs) have provoked intense research because of their superior stability, excellent optoelectronic properties, cost-effectiveness, and striking optoelectronic applications. Recently, the doping of lanthanide ions in IHPs has...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 194 publications
0
33
0
1
Order By: Relevance
“…[ 101 ] However, compared with Pb based halide perovskite, Cs 2 AgInCl 6 shows broad PL originated from the self‐ trapped excitons, with rather low photoluminescence quantum yield (PLQY). [ 1 ] In 2018, Na + alloying and Bi doping were first designed to significantly improve PLQY. Very stable warm‐white light had been realized for 0.04% Bi alloyed Cs 2 (Ag 0.60 Na 0.40 )InCl 6 crystals, with 86 ± 5% quantum efficiency and stability for over 1000 hours.…”
Section: Growth Defects and Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 101 ] However, compared with Pb based halide perovskite, Cs 2 AgInCl 6 shows broad PL originated from the self‐ trapped excitons, with rather low photoluminescence quantum yield (PLQY). [ 1 ] In 2018, Na + alloying and Bi doping were first designed to significantly improve PLQY. Very stable warm‐white light had been realized for 0.04% Bi alloyed Cs 2 (Ag 0.60 Na 0.40 )InCl 6 crystals, with 86 ± 5% quantum efficiency and stability for over 1000 hours.…”
Section: Growth Defects and Dopingmentioning
confidence: 99%
“…In the past decade, metal halide perovskites are undoubtedly one class of the most fascinating optoelectronic materials, thanks to their extraordinary properties, such as outstanding carrier transport characteristics, large X-ray attenuation coefficients, high light-harvesting capability, tunable bandgaps, and highly efficient luminescence. [1,2] Most importantly, metal halide perovskites can be synthesized readily in the form of single crystals, films, nanocrystals, and quantum dots. These outstanding characteristics endow them as emerging candidates for solar cells, LED, lasers, photodetectors, direct/indirect radiation detectors, and photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[64][65][66] Besides this, DC materials doping also contributes to preferable energy-level alignment and also diminishes trapstate density in PSCs. [67][68][69] Moreover, DC materials doping aids the development of perovskite grains with lesser defects. [70] Currently, solar cells include spectrum conversion layers to facilitate the conversion of higher to lower photon energy and vice versa, known as DC and upconversion (UC) processes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Lead halide perovskite nanocrystals (NCs) are some of the most actively researched materials due to the wide range of their applications, including but not limited to optoelectronics, nonlinear optics, photovoltaics, catalysis, sensing, and quantum information technologies. In recent years, significant attention has been paid to the doping of perovskite NCs as a strategy to improve their structural and optical properties. , For example, it was shown that the B-site doping of an ABX 3 perovskite structure can improve the NCs stability, , photoluminescence (PL) quantum yield, and nonlinear response. , Of particular promise is the doping of perovskite NCs with manganese or lanthanides, which results in completely new emission bands in the visible and near-infrared (NIR) spectral ranges, thus making such NCs promising candidates for white light generation, solar harvesting, and bioimaging. Importantly, lanthanide-doped (Yb 3+ and Er 3+ ) NCs can demonstrate an efficient dual-band PL with emission in the visible and NIR spectral regions simultaneously.…”
Section: Introductionmentioning
confidence: 99%